A Review of Students' Interest in Learning about the Sport of Tennis in Sports and Health Education University of Pasir Pengaraian - Manurizal, Lolia; Bakhtiar, Syahrial; Damrah, Damrah (Indonesian Journal of Sport Management, 2024)
The purpose of this study was to determine the Student Learning Interest in Tennis Sports Education Sports and Health at Pasir Pangaraian University. The method used in this research was descriptive quantitative. This research was conducted at Pasir Pangaraian University Sports and Health Education. Data collection was carried out by providing questionnaires about student learning interest in tennis of sports and health education at Pasir Pangaraian University. The type of data analysis uses data analysis techniques using percentage techniques and data processing by determining the number of interval classes and the length of the interval class in weighting following Sturges' rules. The results of this study indicate that students' interest in learning tennis is obtained as many as 3 people (8%) are in the very high category, 10 people (26%) are in the high category, 14 people (36%) are in the medium category, 7 people (18%) are in the low category, and 5 people (13%) are in the very low category.